Omnichannel diagnosis for micro, small and medium-sized companies, sectorial study - Valencia Cárdenas, Marisol; Restrepo Morales, Jorge Anibal; López Cadavid, Diego; Vanegas López, Juan Gabriel (Cuadernos.info, 2024)
The study aims to explain the omnichannel characteristics and behaviors of micro, small and medium-sized enterprises (MSMEs) in the food sector in Antioquia, Colombia. It evaluates the conditions necessary to achieve an omnichannel classification based on three dimensions: marketing models, multichannel options, and supply chain with digital technologies. An explanatory methodology using empirical data from surveys of 140 MSMEs was applied, and cluster analysis was used to group the companies. The results show relatively low overall omnichannel behavior, with medium enterprises outperforming small and micro enterprises. Enhanced digital technologies and integrated platforms can significantly improve omnichannel conditions, leading to better profitability and customer retention. The findings emphasize the importance of digital integration and the need for further research into the technological and methodological aspects of omnichannel implementation.